The effect of clothing and carrion biomass load on decomposition and scavenging in a forensically significant thicketed habitat in Cape Town, South Africa - Jan Spies, Maximilian (Department of Human Biology, 2023)
Estimating the post-mortem interval is important to help identify the deceased in forensic death investigations and requires biogeographically specific knowledge of the rate of decay. Decomposition is influenced by numerous variables, including clothing, climate, and vertebrate scavenging guilds, requiring local studies. Conflicting results have been reported for clothing's effect on decomposition from various international habitats, with no data for Cape Town, South Africa, despite most local forensic cases involving single clothed decedents. Most taphonomic research uses large samples of unclothed human/animal remains to increase statistical reliability, despite this design not simulating common forensic scenarios. This study examined the effect of seasonally appropriate clothing and carrion biomass load on decomposition and scavenging in the thicketed Cape Flats Dune Strandveld, a forensically significant local habitat. Clothing was identified from forensic case files and tailored to ensure an appropriate fit, preventing unrealistic scavenger access. The decay of ten ~60 kg porcine carcasses, as proxies for human decomposition, was quantitatively examined using daily weight loss. This occurred over two consecutive summers and winters between 2018 and 2020, initially comparing clothed versus unclothed carcasses, then examining single clothed carcasses to ascertain the effect of carrion biomass load. On average, double-layer coolweather clothing notably delayed decomposition in winter, but single-layer warm-weather clothing had a comparatively negligible impact in summer. Weight loss correlated with scavenging activity by the Cape grey mongoose (Galerella pulverulenta), which displaced clothing to feed on the abdomen, more so during winter. Scavenging was hindered by the denim trousers, altering feeding patterns and causing preferential scavenging on unclothed carcasses. Single carcasses received more, longer mongoose visits and decomposed quicker than multi-carcass deployments. These results suggest that clothing delays decomposition locally by modulating the effect of seasonal weather and scavenging behaviour. Additionally, research forgoing forensic realism, with large unclothed samples deployed simultaneously, will inadvertently alter the decay rate, creating inaccurate decomposition models for postmortem interval estimation. Future studies should balance statistical robusticity and forensic realism, especially in environments where scavenging is prevalent. Single carcasses clothed in forensically realistic season-specific appropriately tailored clothing should be considered with statistical replication obtained via temporally separated repeat deployments.